Spectroscopic Techniques Study on the Quenching Mechanism of Cytochrome B5 Affected by Cu(II) - Tang, Q.; Peng, X.J.; Cao, H.Y.; Zheng, X.F.; Wang, J.Y. (Asian Journal of Chemistry, 2012)
The interaction between Cu2+ and cytochrome b5 (cytb5) has been investigated by multi-spectroscopic techniques. The results show that Cu2+ could interact with cytochrome b5 and induce fluorescence of the latter to be quenched. The quenching mechanism is dominated by dynamic quenching. Synchronous fluorescence and circular dichroism spectra demonstrate that Cu2+ could also influence the micro-circumatance of aromatic amino residues and secondary structure of the protein.